Riley-Smith, Jonathan Simon Christopher. Templars and Hospitallers as Professed Religious in the Holy Land - Salles, Bruno Tadeu (História Revista, 2012)
R Hospitallers as Professed Religious in the Holy Land University of Notre Dame Press, 2009 (134 páginas) iley-Smith, Jonathan Simon Christopher. Templars and. Indiana: